RNase L Interacts with Filamin A To Regulate Actin Dynamics and Barrier Function for Viral Entry - Krishnamurthy Malathi (American Society for Microbiology, 2014)
ABSTRACT The actin cytoskeleton and its network of associated proteins constitute a physical barrier that viruses must circumvent to gain entry into cells for productive infection. The mechanisms by which the physical signals of infection are sensed by the host to activate an innate immune response are not well understood. The antiviral endoribonuclease RNase L is ubiquitously expressed in a latent form and activated upon binding 2-5A, a unique oligoadenylate produced during viral infections. We provide evidence that RNase L in its inactive form interacts with the actin-binding protein Filamin A to modulate the actin cytoskeleton and inhibit virus entry. Cells lacking either RNase L or Filamin A displayed increased virus entry which was exacerbated in cells lacking both proteins. RNase L deletion mutants that reduced Filamin A interaction displayed a compromised ability to restrict virus entry, supporting the idea of an important role for the RNase L-Filamin A complex in barrier function. Remarkably, both the wild type and a catalytically inactive RNase L mutant were competent to reduce virus entry when transfected into RNase L-deficient cells, indicating that this novel function of RNase L is independent of its enzymatic activity. Virus infection and RNase L activation disrupt its association with Filamin A and release RNase L to mediate its canonical nuclease-dependent antiviral activities. The dual functions of RNase L as a constitutive component of the actin cytoskeleton and as an induced mediator of antiviral signaling and effector functions provide insights into its mechanisms of antiviral activity and opportunities for the development of novel antiviral agents. IMPORTANCE Cells constantly face and sample pathogens on their outer surface. The actin cytoskeleton and interacting proteins associate with the cell membrane and constitute a barrier to infection. Disruption of the actin cytoskeleton allows viruses to enter the cell and induces innate immune responses to clear infections. The molecular mechanisms that link virus-induced physical perturbations to host defense pathways remain unclear. Our studies identified a novel interaction between the antiviral endoribonuclease RNase L and the actin-binding protein Filamin A that enhances host defense by preventing viral entry into naive cells. This role for RNase L is independent of its enzymatic function. Virus infection alters actin dynamics, disrupts the RNase L-Filamin A complex, and releases RNase L to mediate antiviral signaling and effector functions via its established nucleolytic activities. These dual roles for RNase L provide an efficient strategy to protect cells from infection and rapidly respond upon pathogen exposure.